(untitled) (Research, Society and Development, 2021)
Introduction: Health education is a complex practice in which the traditional method declines. Diabetes Mellitus, specifically in home insulin therapy, the improvement of health education enables better results. Objective: to analyze health education actions for insulin therapy at home take place. To this end, the objective was to describe health education methods and identify facilities and difficulties in the practice of home insulin therapy, according to the patient. Methods: This is a descriptive, qualitative study. Semi-structured interviews and, as a complement, unsystematic observation were used, analyzed according to Bardin’s Content Analysis technique. 21 interviews were conducted, with the first calibration of the instrument and the sample defined by data saturation. Results: The traditional methodology of health education prevails among educational actions. Autonomy of self-administration and family participation facilitated adherence to home insulin therapy. Fear of the “pierced”, adverse effects of the administration and hypoglycemia appeared as difficulties of this practice. Conclusion: Difficulties and facilities for home insulin therapy may support the planning of health education aiming at better therapeutic results. Medicine was also identified as an area with little involvement in educational activities.